Innovations in the localization techniques for non-palpable breast lesions: Make invisible visible - Quankun Lin; Qiwen Hou; Chenyu Zhang; Wei Zhai; Feng Cheng; Sen Lu; Xuan Yang; Aiping Dong; Baosan Han (Breast)
Non-palpable breast cancer lesions pose a challenge for surgeons to resect cancer lesions. Making ‘invisible’ lesions ‘visible’ is the main strategy. Currently, multiple preoperative localization techniques have been applied in clinical. Among them, wire-guided localization (WGL) is the most common procedure due to its convenience and low cost. However, its limitations including discomfort, wire migration and the coupling of localization and operation procedures cause troubles for surgeons and patients. The desire for localization methods improvement, accompanied by the advance of emerging science and technology, leads to the development of a series of locating approaches for breast non-palpable lesions, aiming to improve locating accuracy while reducing adverse events. These emerging methods have undergone improvements from steel wire to functional particles, from radioactivity to non-radioactive, which help doctors and patients choose a more appropriate scheme. This review outlines the principles, procedures, advantages and disadvantages of these locating methods, and highlights the latest progress and related clinical data on innovative locating approaches. Finally, we briefly discuss the current challenges and future opportunities for the clinical application of these localization approaches.